IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION DESA WISATA KETAPANRAME DALAM UPAYA MENARIK MINAT BERKUNJUNG WISATAWAN - Rahayu, Annisa Eka; Tatak Setiadi (The Commercium, 2025)
The rapid development of the tourism sector has led to the creation of various types of tourism in Indonesia. One type that is still much favoured by the public is the type of village tourism. The mushrooming of tourist villages in Indonesia today, makes the need for an integrated marketing communication strategy so that later the tourist village can compete with other tours. This research aims to find out the implementation of Integrated Marketing Communication (IMC) carried out by Ketapanrame Tourism Village in its efforts to attract local and foreign tourists. The method used in this research is descriptive qualitative with the type of research, namely case study. Data obtained through the process of interviews with sources, observation, and documentation. The results of the study stated that the most dominant IMC implementation carried out by Ketapanrame Tourism Village was the promotion of discounts through social media and agents, followed by publicity through social media and mass media, the holding of cultural events, and promotion through WOM and E-WOM.